METAL NANOPARTICLES AND ANTIBIOTICS: VALORIZATION OF SYNERGISTIC INTERACTION AND APPLICATION PROSPECTS - Khrokalo, Людмила; Sulyma , Дар’я (Biota. Human. Technology, 2024)
Antibiotic resistance has become a global problem arising from the evolutionary adaptation mechanisms of microorganisms. As a result, there is a constant need to find new solutions, such as developing new drugs or establishing synergistic interactions. Purpose of the work: critical analysis of research paper in the direction of metal nanosystems antimicrobial actions, testing their activity in combinations with different antibiotics, and as a result, synergistic action assessment. Methodology. Present paper reviews the antibacterial mechanism of action of various metals and their oxides nanoparticles, their biomedical applications, toxity potential and methods of NP synthesis. It analyzes and systematizes modern classes of antibiotics, including both commonly used and special groups obtained by genetic engineering. The structural features of the antibiotic molecules with functional atom groups that ensure their antibacterial mechanisms are also reviewed. Innovative approaches to the synthesis of «antibiotic-metal NP» systems are analyzed, and four main methods of obtaining such complexes are highlighted. Scientific novelty. Hypotheses explaining the mechanism of synergistic interaction between NPs and antibiotics of different classes have been analysed. It is shown that the synergistic effect arises from the increased permeability of cell walls and membranes, the enhanced local concentration of metal ions in the cytoplasm, and the conjugation of «antibiotic–metal NP» complexes with bacterial nucleic acids. Conclusions.The obtained results hold promise for clinical practice in developing new therapeutic methods and combating antibiotic resistance. Conclusions regarding the main requirements for creating complex «antibiotic–metal NP» pharmaceuticals are formulated. It is expected that the established synergism will lead to a reduction in effective doses, which will in turn reduce toxicity and undesirable side effects of the innovative complex.